The Impact of Urban Land Use Changes on the Morphology of the New Calabar River Catchment, Port Harcourt Metropolis, Nigeria - Abali, Temple Probyne; Nkii, Lucky Baripara (International Journal of Environment, Engineering and Education, 2024)
The New Calabar River catchment has experienced significant alterations in land use and land cover patterns due to the fast population growth in Port Harcourt. This research investigated the influence of urban land use change on the morphological structure of the New Calabar River basin, which is experiencing rapid urbanization in Rivers State. The research utilized a combination of primary and secondary data sources, specifically satellite imagery and field measurements of the hydro-geomorphic channel's breadth and depth. The findings indicated a significant rise in urbanization, resulting in the encroachment upon various land uses, including water bodies, farmlands, dense forests, and wetlands. Moreover, correlation and regression analysis revealed a significant positive link between channel morphology, discharge, and urbanization index. Therefore, it can be argued that the urbanization index and discharge are crucial in determining the river channel's current channel form and size features. The study also demonstrated a positive correlation between discharge and channel dimensions, including width and depth. The stream channel has experienced an expansion in reaction to the modification of the natural soil caused by urbanization, leading to changes in the stream flow regime. Additionally, it has been observed that the segment of the New Calabar River that encompasses urbanized regions tends to have a comparatively more significant cross-sectional channel. Incorporating urbanization analysis and its impact on morphology has facilitated the implementation of diverse geospatial analyses and sustainable watershed management in the basin.